Fuzzy Boundaries in Discourse Studies
XVII, 318 p. 48 illus., 30 illus. in color.
Keywords: This book focuses on the multifarious aspects of ‘fuzzy boundaries’ in the field of discourse studies, a field that is marked by complex boundary work and a great degree of fuzziness regarding theoretical frameworks, methodologies, and the use of linguistic categories. Discourse studies is characterised by a variety of theoretical frameworks and disciplinary fields, research methodologies, and lexico-grammatical categories. The contributions in this book explore some of the nuances and implications of the fuzzy boundaries in these areas, resulting in a wide-reaching volume which will be of interest to students and scholars of discourse studies in fields including sociology, linguistics, international relations, philosophy, literary criticism and anthropology. Péter B. Furkó is Associate Professor in English Applied Linguistics and Vice Dean for Science and Research at the Department of English Linguistics at Károli Gáspár University of the Reformed Church, Hungary. Ildikó Vaskó is Associate Professor at the Department of Scandinavian Studies at Eötvös Loránd University of Budapest, Hungary. Csilla Ilona Dér is Associate Professor at the Department of Hungarian Linguistics, Károli Gáspár University of the Reformed Church, Hungary. Dorte Madsen is Associate Professor at the Department of Management, Society and Communication at Copenhagen Business School, Denmark.